SRC 2021
DOI: 10.52460/src.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble of Classifiers and Term Weighting Schemes for Sentiment Analysis in Turkish

Abstract: With the advancement of information and communication technology, social networking and microblogging sites have become a vital source of information. Individuals can express their opinions, grievances, feelings, and attitudes about a variety of topics. Through microblogging platforms, they can express their opinions on current events and products. Sentiment analysis is a significant area of research in natural language processing because it aims to define the orientation of the sentiment contained in source m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…Other works have been conducted on fairness for text classification tasks. Some researchers [ 15 ] analyzed different sentiment analysis techniques on the Turkish language with supervised and unsupervised ensemble models to explore the predictive efficiency of the term weighting schemes which is a process to compute and assign a numeric value to each term. The results indicated that supervised term weighting models can outperform unsupervised models in term weighting.…”
Section: Related Workmentioning
confidence: 99%
“…Other works have been conducted on fairness for text classification tasks. Some researchers [ 15 ] analyzed different sentiment analysis techniques on the Turkish language with supervised and unsupervised ensemble models to explore the predictive efficiency of the term weighting schemes which is a process to compute and assign a numeric value to each term. The results indicated that supervised term weighting models can outperform unsupervised models in term weighting.…”
Section: Related Workmentioning
confidence: 99%
“…e Naive Bayes classifier is commonly used in many applications like sentiment classifications and in different ensemble prediction models [16][17][18].…”
Section: Naive Bayesmentioning
confidence: 99%
“…Deneysel analizde, Türkçe Twitter mesajları içeren, terim ağırlıklandırma yöntemlerinin duygu analizi alanındaki etkinliklerini değerlendirmek amacıyla oluşturulmuş bir veri seti kullanılmıştır [22]. Veri seti, 10,500'ü olumlu ve 10,500'ü olumsuz olmak üzere 21000 Twitter mesajı içermektedir.…”
Section: Deneysel Sonuçlar Ve Tartışmaunclassified
“…Derlem için, açıklayıcılar arasında mükemmel bir uyum olduğunu gösteren 0.82'lik bir puan elde edilmiştir. Veri seti üzerinde [22]'de belirtilen önişleme adımları uygulanarak veri seti, derin öğrenme modelleri ile işlemeye hazır hale getirilmiştir. Derin öğrenme mimarilerinin performansını değerlendirmek amacıyla, doğru sınıflandırma oranı, F-ölçütü, geri çağırma ve hassasiyet ölçütleri kullanılmıştır.…”
Section: Deneysel Sonuçlar Ve Tartışmaunclassified